Three‐dimensional visualization of perlecan‐rich neoplastic stroma induced concurrently with the invasion of oral squamous cell carcinoma. (4th April 2014) - Maruyama, Satoshi; Shimazu, Yoshihito; Kudo, Tomoo; Sato, Kaori; Yamazaki, Manabu; Abé, Tatsuya; Babkair, Hamzah; Cheng, Jun; Aoba, Takaaki; Saku, Takashi
<x xml:space="preserve">Abstract</x> Background We have demonstrated the induction of perlecan‐rich stroma of oral squamous cell carcinoma (SCC) on and after its start of invasion. However, it remains unknown how such a neoplastic stroma is actually arranged in tumor tissues. Methods To this end, tissue microarray samples, in which keratin and perlecan were contrastively labeled by immunohistochemistry, were three‐dimensionally analyzed using digital images and image analysis software to demonstrate the relationship between SCC foci and the perlecan‐positive stromal space or that between carcinoma in situ (CIS) and invasive SCC foci. Results The three‐dimensional (3D) reconstruction demonstrated three kinds of perlecan profiles for inside (I) and outside (O) areas of the carcinoma cell focus: mode 1, I+/O−; mode 2, I+/O+; and mode 3, I−/O+. Mode 1 was seen in CIS as well as SCC tumor massifs in the surface part. Mode 2 was seen in small SCC foci, which seemed isolated in 2D sections but were mostly continuous with the tumor massif in 3D reconstructions. Mode 3 was limited to small SCC foci, which were truly segregated from the tumor massif. Conclusions The results indicated that the 2D SCC focus isolation could not be regarded as invasion but that the SCC foci surrounded by perlecan‐positive stroma (modes 2 and 3) could be regarded as a more objective measure for invasion of SCC. This is the first 3D tissue‐level demonstration of the neoplastic stroma space induced with oral SCC invasion, the presence of which we have predicted based on our previous 2D and tissue culture evidence.